Adsorption of Acetylene on CuCl(111) Surfaces Using Density Functional Theory - Jiang, Lihua; Kang, Lihua; Dai, Bin; Zhang, Jinli (Asian Journal of Chemistry, 2013)
Density functional theory and periodic modeling structure were used to study the adsorption of acetylene. Four possible adsorption sites have been considered: Top-Cu, Hollow-CuCl, Bridge-CuCl and Top-Cl sites. For each case, adsorption energies, optimized geometries and vibrational frequencies have been calculated and compared with the experimental data. The calculated results indicate that the Bridge-CuCl site is the most stable adsorption site for C2H2 and the calculated energy is 27.05 kJ/mol.